First outputs of the research project “Universitabile: survey on the social inclusion of students with disabilities and SLDs in the Roman university context” - Antonelli, Carlotta (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
The proposal presents the results of the doctoral thesis “Universitabile,” with population students with disabilities and SLD enrolled in A.A. 2020-2021 at La Sapienza, Tor Vergata and RomaTre. The research aims, on the one hand, to explore and describe the factors that incidate the inclusion and university performance of young people with disabilities and SLD, and on the other hand, to analyze the role of study support services. Since the beginning of the 21st century, Italian universities have been increasingly plural places (Bolt and Penketh, 2016) and have to deal with diversity and the ways in which students with disabilities or DSA are included (Oliver and Barnes, 2010). Here we hypothesize that university policies may produce ambivalent effects (Piccone Stella, 2003). The investigation aims to assess how accessibility to facilities and quality of services contribute to physical and social inclusion, through the use of mixed methods (Mauceri, 2017).